2009
DOI: 10.1021/bi901387k
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Expression of Human Poly(ADP-ribose) Polymerase-1 in Saccharomyces cerevisiae and Identification of PARP-1 Substrates by Yeast Proteome Microarray Screening

Abstract: Poly(ADP-ribosyl)ation of various nuclear proteins catalyzed by a family of NAD(+)-dependent enzymes, poly(ADP-ribose) polymerases (PARPs), is an important posttranslational modification reaction. PARP activity has been demonstrated in all types of eukaryotic cells with the exception of yeast, in which the expression of human PARP-1 was shown to lead to retarded cell growth. We investigated the yeast growth inhibition caused by human PARP-1 expression in Saccharomyces cerevisiae. Flow cytometry analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
(70 reference statements)
1
21
0
Order By: Relevance
“…We found that an alternative approach, using biotin-NAD + for metabolic labelling, was not feasible, because living cells did not take up biotin-NAD + nor could we use digitonin-permeabilised cells for our constitutively-present modifications. (4) Yeast proteasomes, which lack PAR [19], were unmodified on CTAB-PAGE (FigureS4C). However, the modification of human nuclear proteasomes also differs from PAR in several respects: (1) Complete resolution of modified nuclear proteasomes into single subunit bands using PAR enzymes was never achieved (FigureS4A), even when combined and under a wide variety of experimental conditions.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…We found that an alternative approach, using biotin-NAD + for metabolic labelling, was not feasible, because living cells did not take up biotin-NAD + nor could we use digitonin-permeabilised cells for our constitutively-present modifications. (4) Yeast proteasomes, which lack PAR [19], were unmodified on CTAB-PAGE (FigureS4C). However, the modification of human nuclear proteasomes also differs from PAR in several respects: (1) Complete resolution of modified nuclear proteasomes into single subunit bands using PAR enzymes was never achieved (FigureS4A), even when combined and under a wide variety of experimental conditions.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…Numerous studies suggested that PARylation also plays active roles in regulating ribosomal DNA (rDNA) transcription [52,53] and ribosomal biogenesis [49,54,55] in the nucleoli. Poly(ADP-ribose) binds to several rRNA-associated nucleolar proteins, including Fibrillarin, Nucleolin and Nucleophosmin in Drosophila nucleoli [49].…”
Section: Post-transcriptional Molecular Events Regulated By Parylamentioning
confidence: 99%
“…Indeed, disruption of pADPr metabolism by either PARP1 or PARG loss-of-function causes mislocalization of these proteins and nucleolus fragmentation, which further results in rRNA processing defects [49]. In addition, six yeast nucleolar proteins (UTP7, BUD21, Nob1, Has1, Nop53 and LHP1) have been identified to be PARylated upon expression of human PARP1 in yeast ( S. cerevisiae ), which lacks functional PARP homologues [55]. Therefore, these results suggest that pADPr may serve as a matrix to attract rRNA-binding proteins to the nucleoli for ribosomal biogenesis [49].…”
Section: Post-transcriptional Molecular Events Regulated By Parylamentioning
confidence: 99%
“…Interestingly, they also found that inhibition of glycosylation by N-linked glycosylation inhibitor tunicamycin affected the localization of some mitochondrial proteins, such as Ydr065wp and Lpe10p, which suggests that proper protein glycosylation is important for their normal localization and function. In addition to glycosylation, Tao et al used an analogous approach to examine poly(ADP-ribosyl) ation in yeast with protein microarray [85]. Poly(ADP-ribosyl) ation of proteins is usually carried out by the enzyme poly(ADPribose) polymerase-1 (PARP-1), a pluripotent enzyme involved in both DNA damage sensing mechanism and regulation of gene expression [86,87].…”
Section: Detection Of Post-translational Modifications Using Protein mentioning
confidence: 99%